Geothermal Potential of the Dimanjar District, Sumberarum,Tempuran Area Using Resistivity and Geochemical Data Approaches - Fatimah; Trisnaning, Paramitha Tedja; trianda, obrin (Journal of Geoscience, Engineering, Environment, and Technology, 2025)
Hot springs in geological science are associated with geothermal manifestations. The appearance of these hot springs indicates certain geological conditions in the area. In the Dimanjar area, Sumberarum sub-district, Tempuran sub-district, Magelang regency, there are hot springs which residents use for tourism. This research is about the geochemistry of hot springs and looks at the depth of hot springs using the Schlumberger configuration geoelectric method. There are two Schlumberger measurement lines, namely west east and north south, this is because the measurement target or the presence of the spring is perpendicular to the Ngasinan River. The data shows that there are two salt water aquifers at depths of 20-30 meters and 130 meters with resistivity values below 0.5 ohm meter, which is theoretically the resistivity of salt water. Geochemical data also shows that the Cl content is high and this is a mature hot spring. This geochemical data was analyzed from the chloride values of 10 hot springs that emerged both naturally and through drilling. Plotting data in a trilinear triangle indicates the water source comes from a reservoir. The data shows that all water samples are of the chloride type in the range of 40% to 10% mature water. Subsurface and subsurface data show that there are two saltwater aquifers that are quite far apart in depth, this could be due to developing tectonics.